The Bank Capital Debate: Should Fragility Be Reduced? - Philipp König; David Pothier (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
The recent financial crisis has exposed the fragility of the banking sector to sudden withdrawals of wholesale funding, asset price declines and market dry-ups. Governments and central banks had to step in to prevent major banks from defaulting. These events led to renewed interest in the question whether the fragility of banks should be tolerated as a necessary, even desirable feature of an efficient process of financial intermediation, or whether banks should be subject to stricter regulation ex ante. This Round-Up summarizes the key arguments on both sides of the debate.
Keywords: 330